Wireless networks first-step - Geier, James T. (First-step series., 2005)
Your First-Step into the World of Wireless Networks No experience required! Gain an understanding of wireless networking basics with this reader friendly guide The first book anyone should read about wireless networks with step-by-step instruction Learn from an author experienced in and known for writing to a generalist wireless audience with a clear, simple-to-understand style As a basic introduction to wireless networking, Wireless Networks First-Step assumes that readers have no previous wireless experience. The book provides an overview of wireless networking, along with details of applicable standards and technologies. Newcomers to wireless technologies will find practical information along with an abundance of examples. Case studies throughout the chapters provide real-world implementation examples, presented in a non-technical fashion. Implementation details are discussed only to the extent that readers can identify what type of wireless network may be appropriate for their needs. Wireless Networks First-Step , written by Jim Geier, begins with a basic introduction to wireless networks and an explanation of radio wave communications. It then reviews different types of wireless networks including WPANs (wireless personal area networks), WLANs (wireless local area networks), wireless MANs (metropolitan area networks), and WWANs (wireless wide area networks). The final section covers security threats to wireless networks, and solutions to combat these threats. 158720111903232004